Stability region characterization of a two-user age of information restricted cognitive radio model - Mohamed, Ali Gaber; Gamal, Mahmoud (Alexandria engineering journal, 2023)
In this paper, we consider stability and latency analysis of a two-user cognitive radio network while considering Age of Information requirements imposed on the data transmissions of the users. We provide two different formulations. In the first formulation, our objective is to maximize the stable throughput of the secondary user subject to Age of Information constraints imposed on the data transmission of the users. While, in the second formulation, we introduce a multi-objective programming approach that investigates the trade-off between the secondary user stable throughput and its Age of Information. Our numerical results characterize the effect of imposing different Age of Information restrictions on the stable throughput region of the network; we show that the stability region, in certain cases, is reduced by only 11% with strict Age of Information restrictions. Our results also investigate the trade-off between the secondary user throughput and the Age of information. Finally, our results show the potential accuracy of the algorithm adopted in this paper to solve the formulated non-linear optimization problems.